The Contribution of Authoritarian Parenting Perceptions on High School Students' Confidence - Tita Setiya Wati; Komarudin Komarudin (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
Having self-confidence is very necessary in living life in order to be able to pass the stages of development well. Appearing with confidence is one of the keys to success in living life with a social environment such as friends and society. Without self-confidence, individuals will experience many problems within themselves. One of the factors that influence self-confidence is interaction and parenting applied by parents. The purpose of this study was to determine the relationship between perceptions of authoritarian parenting and self-confidence in high school students in Yogyakarta. This study uses a quantitative method with a correlation approach. Respondents in this study were high school students in Yogyakarta. The number of respondents as many as 80 students. The sampling technique used was purposive sampling. Data retrieval using scale filling. Data analysis using Pearson Product Moment correlation. The results showed that respondents had a perception of authoritarian parenting in the medium category with a percentage of 86.3% (69 people), while the respondents' self-confidence was at a moderate level with a percentage of 85% (68 people). Based on the data on the results of the determination test (R Square) which shows that the test results (R²) are worth 0.115 or 11.5%. Perceptions of authoritarian parenting contributed 11.5% to self-confidence. There is a significant negative relationship between the perception of authoritarian parenting and self-confidence in high school students in Yogyakarta. So that the higher students' perceptions of authoritarian parenting, the lower their self-confidence, and vice versa, the lower students' perceptions of authoritarian parenting, the higher their self-confidence.